Active methodologies in geography: teaching experiences of the federal institute of education, science and technology of ceará (ifce) - Lima, Anna Erika Ferreira; Silva, Danielle Rodrigues da; Araújo, Enos Feitosa de (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
The use of active methodologies has been configured as an alternative to involve and stimulate students in the learning process. In the Federal Institute of Ceará, the number of students dropping out and/or learning and adaptation difficulties to profile of the student of integrated middle courses, instigated to adoption of pedagogical practices that sought to more effectively enable these students.Thus, the active methodologies became part of daily life of many Geography classes. The present work has as general objective to report the main active methodologies used in the teaching Geography developed by professors from Fortaleza, Umirim and Quixadá campuses in the period 2016-2017. For the accomplishment of work, we divide it into three stages, namely: 1) Literature review; 2) Application of questionnaires, selection of methodologies to be used and execution of the same; 3) Systematization and analysis of experiences. The most attractive active methodologies for the 61 students who participated in the research is: a) Simulated jury; b) field classes / technical visits; c) World Coffee; and d) Flipped Classroom. So, in the expectation of contributing to the adoption of more contextualized and closer to students' understanding, the active methodologies became part of the daily life of many of the Geography classes.